APLIKASI TUNTUNAN LAGU QIRAâATIL QURâAN BERBASIS ANDROID - Yunus, Muhammad; Affandi, Luqman; Farida, Eny (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2014)
Application of the Quran is one of the many programs developed to play store. However, application of the art of reading the Quran is still not a lot, especially on android based applications, whereas science is necessary for every Muslim to and the qori and qoriah, Learning the art of the song read the Quran it is difficult. Therefore, the teacher or teachers, especially in Quranic Education Park (TPA) difficulty in learning and searching qiraatil quran tutor. They do not care as long as the distance traveled to meet and study with qiraatil quran tutor. Art program read the Koran has advantages compared with other applications because it can run on all android devices. Making this program by using several methods: data collection methods, design methods, and methods of implementation. Where the method of data collection consisted of: interviews, literature, and analysis, while the design method consists of tracing requirements phase, analysis phase, the design phase of the application, and the phase of making the application, and for the implementation of the method comprising: coding phase, testing phase and evaluation phase. Application art of reading the Quran can be used as a guide to reading and understanding the art of reading the Quran as well as a variety of songs from qiraatil Quran.Â Keywords: Android, Qiraatil Quran, Tausyih